TRENDS OF LEGAL EDUCATION REFORM IN LATVIA - Gaveika, Artūrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In 2015 the Ministry of Justice of the Republic of Latvia initiated reform of legal education in Latvia in order to achieve higher quality of legal education. As the most appropriate reform tool to solve this problem, a single lawyer qualification examination and the elimination of the profession of legal adviser were adopted. At the beginning of these reforms, there was no detailed study of the reasons for the lack of quality in legal education and was not audited the study programs of the relevant higher education institutions. The quality of legal education in Latvia has become a subject of public discussion for a considerable amount of time. In 2017, the Rezekne Academy of Technologies was forced to start new study programs development due to elimination of the profession of legal adviser and to create additional opportunities for student quality education in connection with the implementation of a single lawyer's professional qualification examination. The article is dedicated to issues and perspectives of legal education reforms. The study used: the method of legal analysis, studying the progress of legal education reforms, requirements of regulations in the context of the topic and analyzing the quality of legal profession standards and compliance of society, the national economy needs and the impact on the content of study programs in RTA and other higher educational institutions. The comparative method has been used to find out and compare the opinions of experts - employers, university lecturers and students, including RTA students.